2011
DOI: 10.1200/jco.2009.26.4473
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Insulin Resistance and Adiponectin With Mortality in Women With Breast Cancer

Abstract: A B S T R A C T PurposeOverweight or obese breast cancer patients have a worse prognosis compared with normal-weight patients. This may be attributed to hyperinsulinemia and dysregulation of adipokine levels associated with overweight and obesity. Here, we evaluate whether low levels of adiponectin and a greater level of insulin resistance are associated with breast cancer mortality and all-cause mortality. Patients and MethodsWe measured glucose, insulin, and adiponectin levels in fasting serum samples from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
209
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(222 citation statements)
references
References 54 publications
9
209
2
2
Order By: Relevance
“…In this regard, it should be pointed out that in cancer patients affected by insulin resistance, increased insulin levels combine with frequent INSR overexpression leading to abnormal stimulation of nonmetabolic effects mediated by INSR, such as cell survival, proliferation, and migration (Belfiore & Malaguarnera 2011). For instance, high insulin levels have been associated with an increased risk of breast cancer and breast cancer relapses in diabetic and nondiabetic women (Duggan et al 2011, Cohen & Le Roith 2012, Sieri et al 2012. Taking into account these data and the results of the present study, it would be interesting to evaluate in future studies the actual role performed by estrogenic GPER1 signaling in different pathophysiological conditions characterized by insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it should be pointed out that in cancer patients affected by insulin resistance, increased insulin levels combine with frequent INSR overexpression leading to abnormal stimulation of nonmetabolic effects mediated by INSR, such as cell survival, proliferation, and migration (Belfiore & Malaguarnera 2011). For instance, high insulin levels have been associated with an increased risk of breast cancer and breast cancer relapses in diabetic and nondiabetic women (Duggan et al 2011, Cohen & Le Roith 2012, Sieri et al 2012. Taking into account these data and the results of the present study, it would be interesting to evaluate in future studies the actual role performed by estrogenic GPER1 signaling in different pathophysiological conditions characterized by insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in cancer patients affected by insulin resistance, increased insulin levels combine with frequent INSR overexpression in tumor cells, leading to abnormal stimulation of nonmetabolic effects mediated by INSR, such as cell survival, proliferation, and migration (Belfiore & Malaguarnera 2011). In particular, high insulin levels are associated with an augmented risk of breast cancer and breast cancer relapses in diabetic and nondiabetic women (Duggan et al 2011, Cohen & Le Roith 2012, Sieri et al 2012. It has been well established that a cooperative crosstalk between insulin and estrogen signaling pathways triggers multiple biological events in breast carcinogenesis (Rose & Vona-Davis 2012, Catsburg et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Allele A of polymorphism -308G>A of TNF-α is associated with a high level of in vitro TNF expression and has also been associated with increased susceptibility and severity of various diseases, such as diabetes, immunological diseases, malaria, infection, and cancer (Berberoglu et al, 2004;Duggan et al, 2011;Cereda et al, 2012;Chu et al, 2012). However, the associations between -308G>A TNF-α polymorphisms and BC remain controversial, and their association depends on the population studied.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have suggested that glucose metabolism may contribute to BC development. Because insulin can stimulate cell proliferation through its receptor, it regulates insulin-like growth factor binding proteins and sex hormones, increasing bioavailable mitogens (Duggan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only a few studies-mostly from a single research group-have been performed in cohorts of BC patients with metabolic characteristics comparable to those of the general population, while the majority of the articles available in the international literature have focused on the association between BC and glucose metabolism in patients with clinical features belonging to metabolic syndrome [24,39], obesity [25][26][27]40] or dyslipidemia [28,29], all of which recognize IR as a common factor.…”
Section: Discussionmentioning
confidence: 99%